The potential protective effects of curcumin on the diabetic ovary: Experimental and molecular approaches - Tufekci, Kıymet Kübra; Altun, Gamze; Kipanyula, Maulilio John; Kaplan, Süleyman (Universidad de Murcia, Departamento de Biologia Celular e Histiologia, 2024)
Diabetes mellitus (DM) causes numerous systemic diseases in animals and humans. This may also lead to reproductive problems among individuals of reproductive age. Detrimental effects such as apoptosis in ovarian granulosa cells, degradation of communica-tion proteins, decreased oocyte quality, delayed meiotic maturation, and atrophy are among the increasing evidence that chronic hyperglycemia causes reproductive problems. Numerous studies have reported that the antidiabetic properties of the antioxidant curcumin may be due to its inhibition of oxidative stress, inflammation, and insulin resistance. There are also data indicating that curcumin reduces the risk of DM and its associated symptoms. This review discusses the protective or curative properties of curcumin in the treatment of DM-related problems in the ovary and seeks to elucidate potential underlying mechanisms. While the use of curcumin as a supportive/therapeutic agent has been introduced for the reduction of reproductive problems that may be caused by uncontrolled DM, more studies on this subject are needed.
Keywords: Curcumin; Diabetes mellitus; CDU::6 - Ciencias aplicadas::61 - Medicina::616 - Patología. Medicina clínica. Oncología; Ovary; Female fertility